Restating the role of Alfalfa Integrated Pest Management in Argentina - Frana, Jorge; Trossero, Marcia Andrea; Fava, Fernando Daniel; Trumper, Eduardo Victor (INTA, 2024)
The current concepts within the Integrated Pest Management (IPM) framework stem from the contributions by Stern and collaborators (1959), professors of California University, developed precisely for alfalfa crop. At that time, they designed the integration of chemical control with the biological control of the spotted alfalfa aphid. IPM, based on fast and reliable sampling methods, with economic thresholds determined through field research, and the use of selective insecticides that effectively control the target arthropod species but have minor or no impact on beneficial wildlife, is proposed as a sound strategy to reduce economic loss risks without compromising environmental health. IPM integrates concepts from the economic theory and mainly concepts and hypotheses stemming from the ecology theoretical framework, such as the theory of island biogeography (MacArthur and Wilson, 1967); the theory of natural enemies (Doutt & DeBach, 1964); and the resource concentration hypothesis (Root, 1973).